Pertumbuhan di Pinggiran Kota Kecil: Pola Perkembangan Peri-Urban dan Faktor Pembentuknya (Studi Kasus: Kecamatan Tallunglipu) - Membala, Sarah; Dewi, Dhyah Puspita (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
The wave of urbanization has driven the expansion of areas into suburban regions. Land pressure in suburban areas is not only experienced by metropolitan cities but also occurs in the outskirts of smaller towns. More than 2,400 towns with populations ranging from 1,500 to 5 million are generally categorized as small towns, with 60% of them located in developing regions and countries. The spatial transformation occurring in suburban areas is closely intertwined with the regional dynamics of their administrative capitals (Rantepao). The development patterns in Tallunglipu District exhibit ribbon development and leapfrog development. A synthesis of factors influencing peri-urban development reveals that the peri-urban development patterns in Tallunglipu District are shaped by several factors, including local government policies, physical territorial boundaries, the presence of road infrastructure, the availability of public service facilities, and supporting infrastructure for traditional customs. Identifying the development patterns and determining the driving factors of peri-urban areas in small towns can serve as a preventive and mitigative strategy to prevent development from exceeding the carrying capacity of these small towns.